2004
DOI: 10.1002/art.20121
|View full text |Cite
|
Sign up to set email alerts
|

Association of the interleukin‐1 gene cluster with radiographic signs of osteoarthritis of the hip

Abstract: Objective. To study the role of the interleukin-1␤ gene (IL1B) and the IL-1 receptor antagonist gene (IL1RN) in relation to the occurrence of radiographic osteoarthritis (ROA) in the hip, knee, and hand and disc degeneration of the spine.Methods. The study population consisted of a random sample of 886 subjects (ages 55-65 years) from a population-based cohort (the Rotterdam study). Two polymorphisms within IL1B (3953C>T and ؊511C>T) and one within IL1RN (the variable-number tandem repeat [VNTR]) were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
2
4

Year Published

2004
2004
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 33 publications
2
71
2
4
Order By: Relevance
“…In RA, the association has not been observed in Caucasian patients with RA who are of northern European origin (24,25), but it has been observed in the Spanish population (as reported here). In a smaller-scale study of the same polymorphism, which was performed in a group of RA patients from southern France (26), who are similar both geographically and perhaps genetically to our population, a tendency toward an association of IL1RN*2 and RA was shown.…”
Section: Role Of Il1rn In Ra Susceptibilitycontrasting
confidence: 59%
“…In RA, the association has not been observed in Caucasian patients with RA who are of northern European origin (24,25), but it has been observed in the Spanish population (as reported here). In a smaller-scale study of the same polymorphism, which was performed in a group of RA patients from southern France (26), who are similar both geographically and perhaps genetically to our population, a tendency toward an association of IL1RN*2 and RA was shown.…”
Section: Role Of Il1rn In Ra Susceptibilitycontrasting
confidence: 59%
“…As a direct result of the functional data presented herein and the biologic rationale surrounding IL-1B as a candidate gene for OA, we subsequently investigated the CϪ511T polymorphism for genetic association with hip OA. As described by Meulenbelt et al (25), the T allele at Ϫ511 of the IL1B gene is significantly associated with OA of the hip. These genetic associations are in concor-IL-1␤ GENE PROMOTER POLYMORPHISM AND LEVELS OF IL-1␤ PROTEINdance with the hypothesis that an increase in the levels of IL-1␤ protein secretion due to the genetic variation in the IL-1␤ gene may contribute to the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 74%
“…It is well documented that IL-1␤ plays a role in several inflammatory diseases, such as in the severity of RA and in inflammatory bowel disease (1)(2)(3). In addition, the IL1 gene cluster has been identified as a significant region of linkage to OA of the hand (20), and more recently, Meulenbelt et al (25) demonstrated a significant genetic association between the T allele at Ϫ511 of the IL1B gene and allele 2 in the IL-1RN variable-number tandem repeat and OA of the hip. Polymorphisms within the IL-1 cluster have also been associated with differences in protein levels (18).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have now reported case-control studies in which extended haplotypes in the IL1 gene cluster have been associated with specific features of osteoarthritis (31)(32)(33). Given the low levels of LD seen between IL1A/B and ILRN in our control populations, there is little reason to expect that an extended haplotype spanning this region would be strongly associated with disease.…”
Section: Discussionmentioning
confidence: 88%